Self-esteem and quality of life: a relationship with aesthetics (Research, Society and Development, 2022)
Introduction: In Brazil, the search for a beauty standard is a race against time, every minute there is new information, a new product, a new aesthetic treatment, a new trend, a new style. It is already known that vanity is a great characteristic of the Brazilian people, and the field of the aesthetic area is quite wide, for this reason this work aimed to review the satisfaction of patients after undergoing aesthetic treatments, analyzing their influence on their self-esteem and self-image. , as well as reviewing customer satisfaction after procedures. Methodology: Integrative, bibliographical literature review with research in the Scientific Electronic Library Online and Latin American and Caribbean Literature in Health Sciences databases based on the descriptors: “self-esteem”, “self-image”, “body image” and “aesthetic procedures”. The search period in the databases took place in May and June 2022. The selection of articles followed the following inclusion criteria: scientific articles published from 2015 onwards, in Portuguese and with full text. Articles in periodicals and also course completion papers related to the topic were considered. Results: Finally, ten studies that met all criteria were selected. Conclusion: The works analyzed indicate that aesthetic procedures have positive impacts on the self-image of individuals, with beneficial consequences for their self-esteem and quality of life.